A new risk assessment method of power system distance protection. (9th February 2015) - Dai, Zhihui; Liu, Xuan
Summary: The correct and reliable operation of distance protections is significant to the safety and stability of power systems. Considering that the current failure probability models of distance protection, usually needing complicated calculation, could not accurately reflect the protection principle and the impact of protection coordination on relay failure probability, a new method of calculating the failure probability of distance protections based on the definitions of the starting intercept, the measuring intercept, etc. is proposed first, according to the operation characteristic of impedance relays. A detailed risk assessment flow of distance protection is formulated afterwards, taking into account the consequence of protection failures and risk indices. The distance protection risk assessment of the IEEE 9‐bus system was given finally, and the results show that this approach could be used for evaluating the operating risk, as well as the potential risk of protection systems. Copyright © 2015 John Wiley & Sons, Ltd.